Peripheral Giant Cell Granuloma of Maxilla: A Case Report - Zahra Pourgholi Takrami; Fatemeh Abbasi (Journal of Craniomaxillofacial Research)
Peripheral giant cell granuloma is a benign and reactive hyperplastic lesion originating from the periosteum and resulting from local stimulation or trauma. It is more aggressive due to its high growth potential and may involve the cortical plate. Diagnosis is based on histopathological findings. It occurs mostly in the lower jaw, but can also occur in the upper jaw. It often appears as a nodular purple mass on the gums or mucosa of the edentulous alveolar ridge. we report a case of maxillary peripheral giant cell granuloma with bone resorption in a 46-year-old male patient, who was treated with an excisional biopsy. Keywords: Peripheral giant cell; Reactive; Jaw.